Use of negative pressure wound therapy on surgical incisions (prevena(TM)) after surgery of pectus deformities reduces wound complications - Simon, Kirsten; Schulz-Drost, M.; Besendörfer, Manuel; Carbon, R. T.; Schulz-Drost, S. (Zentralblatt für Chirurgie, 2015)
Pectus surgery can lead to postoperative wound complications in some cases. The purpose of this study is to determine whether preventive negative pressure wound therapy (NPWT) could reduce wound complications after open pectus surgery.100 patients after open procedure for the treatment of pectus excavatum or pectus carinatum in the years 2010 to 2012 were retrospectively analysed. 50 patients treated with Prevena(TM) (KCI Medical Products GmbH, Wiesbaden, Germany) were compared with 50 patients whose wounds were covered with OPSITE® film (Smith & Nephew, Hamburg, Germany). Wound closure was performed following a standard procedure as well as the placement of subcutaneous drains. Therefore two comparable groups of patients were formed and analysed by standardised parameters. The wound dressing was placed epicutaneously immediately after wound closure in the operating room and removed after 5 days in each case. Follow-ups were performed immediately after removal of the wound dressing, at the time of discharge from hospital as well as 6 and 12 weeks after operation. The wounds were checked for tenderness, pain, secretion, redness and fistulas.The Prevena group showed 10 % wound complications which needed operative treatment, whereas the OPSITE group showed complications in 24 %. Some patients who were treated with Prevena showed superficial skin lesions at the rim of the foam and the film. All of these lesions healed well.Treating wounds postoperatively with preventive measures (NPWT) showed a remarkable reduction of wound complications following open pectus surgery whereas statistically the difference was not significant (p = 0.074).
EVALuna2:15835